Incentives and the Supply of Effective Charter Schools - Singleton, John D. (American Economic Review, 2019)
Charter school funding is typically set by formulas that provide the same amount for students regardless of advantage or need. I present evidence that this policy skews the distribution of students served by charters toward low-cost populations by influencing where charter schools open and whether they survive. To do this, I develop and estimate an equilibrium model of charter school supply and competition to evaluate the effects of funding policies that aim to correct these incentives. The results indicate that a cost-adjusted funding formula would increase the share of disadvantaged students in charter schools with little reduction in aggregate effectiveness. (JEL H75, I21, I22, I28)